2022
DOI: 10.1038/s41556-021-00821-8
|View full text |Cite
|
Sign up to set email alerts
|

BRD2 inhibition blocks SARS-CoV-2 infection by reducing transcription of the host cell receptor ACE2

Abstract: SARS-CoV-2 infection of human cells is initiated by the binding of the viral Spike protein to its cell-surface receptor ACE2. We conducted a targeted CRISPRi screen to uncover druggable pathways controlling Spike protein binding to human cells. Here we show that the protein BRD2 is required for ACE2 transcription in human lung epithelial cells and cardiomyocytes, and BRD2 inhibitors currently evaluated in clinical trials potently block endogenous ACE2 expression an… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
80
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(84 citation statements)
references
References 61 publications
4
80
0
Order By: Relevance
“…BRD4 is known to mediate immune and inflammatory responses to viral infection and was recently reported to regulate COVID-19-mediated cytokine storm and cardiac damage ( Mills et al., 2021 ). Furthermore, BET inhibitors were shown to downregulate the expression of viral host entry factors, such as angiotensin-converting enzyme 2 (ACE2), thereby limiting SARS-CoV-2 replication in vitro ( Gilham et al., 2021 ; Qiao et al., 2020 ), and have potent anti-viral activity ( Acharya et al., 2022 ; Qiao et al., 2020 ; Samelson et al., 2022 ). To examine the importance of the BRD4-E interaction for the SARS-CoV-2 life cycle, we infected the human lung bronchial epithelial cell line Calu-3 with a Delta variant of SARS-CoV-2 (pangolin linage B.1.617.2) and monitored infection by immunofluorescence ( Figures 4 A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…BRD4 is known to mediate immune and inflammatory responses to viral infection and was recently reported to regulate COVID-19-mediated cytokine storm and cardiac damage ( Mills et al., 2021 ). Furthermore, BET inhibitors were shown to downregulate the expression of viral host entry factors, such as angiotensin-converting enzyme 2 (ACE2), thereby limiting SARS-CoV-2 replication in vitro ( Gilham et al., 2021 ; Qiao et al., 2020 ), and have potent anti-viral activity ( Acharya et al., 2022 ; Qiao et al., 2020 ; Samelson et al., 2022 ). To examine the importance of the BRD4-E interaction for the SARS-CoV-2 life cycle, we infected the human lung bronchial epithelial cell line Calu-3 with a Delta variant of SARS-CoV-2 (pangolin linage B.1.617.2) and monitored infection by immunofluorescence ( Figures 4 A and 4B).…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies identified 67 potential interactions between host and viral proteins essential for the SARS‐CoV‐2 lifecycle, like BRD2/BRD4 with the E protein of SARS‐CoV‐2, 4 and suggested that BRD2 inhibition downregulates ACE2 expression, blocks the entry of SARS‐CoV‐2 into host cells and controls hyperactive immune response in COVID‐19 patients through downregulation Interferon stimulated genes (ISGs). 5 Targeted therapies that exploit host–virus interaction are likely to be least impacted by the VOCs of SARS‐CoV‐2 and are expected to produce more robust, durable treatment options. Therefore, we tested the anti‐viral potential of SF2523 against the wild‐type SARS‐CoV‐2 and VOCs.…”
Section: Figurementioning
confidence: 99%
“…One of such proteins includes BRD2, which is shown to interact with the E protein of SARS-CoV-2, leading to downregulation of ACE-2 expression that blocks SARS-CoV-2 entry to host cells. 6 Our recent review also emphasizes that SARS-CoV-2 interactions occur at the organelle levels (e.g., mitochondria), and hence mitochondria are also predicted to be emerging as a potential target in COVID-19 treatment. 7 Authors believe that since several SARS-CoV-2 proteins interact with host proteins to escape from being eliminated, strategies like inhibition of host-SARS-CoV-2 protein interaction could block the entry of SARS-CoV-2 and downregulate the cytokine storm by decreasing certain interferon-stimulated genes.…”
mentioning
confidence: 98%